2023
DOI: 10.1039/d2cs00627h
|View full text |Cite
|
Sign up to set email alerts
|

Surface barriers to mass transfer in nanoporous materials for catalysis and separations

Abstract: Nanoporous materials interfaces are the new frontier: understanding and controlling surface barriers to diffusion is key in catalysis and separations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 114 publications
(196 reference statements)
0
5
0
Order By: Relevance
“…Second, it would be interesting to try to interpret the observed rate trend in terms of the rate-determining processes identified in the kinetic analysis, specifically layer diffusion and intraparticle diffusion. However, mass transfer mechanisms into and within microporous materials are complex and not always well-understood . For example, the presence of defects can have profound effects on gas diffusion into and within microporous particles, and although more defects might be expected in the smaller particles, the concentration and types of defects which may be present are not known in the current work.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Second, it would be interesting to try to interpret the observed rate trend in terms of the rate-determining processes identified in the kinetic analysis, specifically layer diffusion and intraparticle diffusion. However, mass transfer mechanisms into and within microporous materials are complex and not always well-understood . For example, the presence of defects can have profound effects on gas diffusion into and within microporous particles, and although more defects might be expected in the smaller particles, the concentration and types of defects which may be present are not known in the current work.…”
Section: Resultsmentioning
confidence: 93%
“…However, mass transfer mechanisms into and within microporous materials are complex and not always well-understood. 42 For example, the presence of defects can have profound effects on gas diffusion into and within microporous particles, and although more defects might be expected in the smaller particles, the concentration and types of defects which may be present are not known in the current work. With regard to layer diffusion, a further complication is that we currently have no knowledge of the structure, dynamics, and depth of the boundary layer at the PDMS-AF interface or how it might vary with particle size (although we note with interest the work of Sheng et al 43 on type 3 porous ionic liquids in which TEM analysis revealed a substantial ∼100−200 nm adsorbed layer of IL at the MOF-IL interface and it is possible that a similar boundary layer exists in PL1−3).…”
Section: Adsorption Diffusion Modelsmentioning
confidence: 96%
“…In the 3DOM/IO structure, some naturally occurring secondary meso- and/or micro- porosity may be created in the macropore walls from volume shrinkage associated with the infiltrating sol–gel precursor during the template removal step, , or when nanocrystals are randomly packed to form the 3DOM/IO structure. , To achieve greater control over the secondary pore structure (i.e., size, placement, connectivity), a second, or even a third template can be intentionally introduced as additional pore-directing agents. ,,,, Secondary porosity not only creates even more surface area for mass transport, but also unlocks size-selective and confined space catalytic features only found in mesoporous and microporous materials due to their substantially higher frequency of reactant–pore wall interactions in anomalous Knudsen diffusion regimes. While NP-containing hierarchical macro-mesoporous structures are typically prepared by hard colloidal templating for thermocatalytic applications, a combined hard–soft templating approach presents unique synthetic advantages to achieve spatially disparate active site localization (see Section ). , …”
Section: Np-containing Hierarchical Macro-mesoporous Structuresmentioning
confidence: 99%
“…We next discussed how to create secondary mesoporosity in 3D macroporous structures to produce NP-containing extended hierarchical macro-mesoporous structures (Figure ) in Section . , Such hierarchical structures exploit the high surface area of macropores for mass transport, together with confined diffusion and size-selective properties in the adjacent connected mesopores. In Section , we discussed how a hierarchical macro-mesoporous structure prescribes a well-defined bulk ↔ macropore ↔ mesopore direction of reactant flow which, when combined with spatially disparate active site placement/functionalization in the different interconnected pore systems, affords highly selective catalytic cascades (Figure ) capable of circumventing antagonistic side reactions (Figure ). , …”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…As a result, the LAS centers confined in the micropores of large crystallites give rise to strong mass diffusion limitations and reduce the accessibility of these sites to bulky reactant molecules. 31–33 To simplify the synthesis procedure and shorten the synthesis period, to improve the accessibility of LAS centers, and to create new types of Lewis acid zeolites with distinct framework structures and heteroatoms, numerous synthetic strategies such as improved direct synthesis and post-synthesis have been developed in recent years. Although the LASs confined in zeolite micropores should theoretically have a uniform structure, the real structure may be varied depending on different synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%